1996
DOI: 10.1111/j.1476-5381.1996.tb15302.x
|View full text |Cite
|
Sign up to set email alerts
|

Increase in action potential duration and inhibition of the delayed rectifier outward current IK by berberine in cat ventricular myocytes

Abstract: 1In the present work, the effects of the antiarrhythmic drug, berberine, on action potential and ionic currents of cat ventricular myocytes were studied. 2 Berberine prolonged action potential duration in cat ventricular myocytes without altering other variables of the action potential. 3 The drug at concentrations of 0.3-30 gM blocked only the delayed rectifier (IK) current with an IC50 = 4.1 gM. Berberine produced a tonic block and a phasic block that was increased with the duration of the depolarizing pulse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…Berberine was earlier described to inhibit hERG potassium current in HEK cells expressing hERG channels [8], to block I Kr current in cardiac myocytes [6], and to increase action potential duration on cardiac preparations [6,7], which are well in line with our findings. Furthermore from this subgroup, we have also studied coptisine, the main alkaloid of C. majus.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Berberine was earlier described to inhibit hERG potassium current in HEK cells expressing hERG channels [8], to block I Kr current in cardiac myocytes [6], and to increase action potential duration on cardiac preparations [6,7], which are well in line with our findings. Furthermore from this subgroup, we have also studied coptisine, the main alkaloid of C. majus.…”
Section: Discussionsupporting
confidence: 82%
“…Among these alkaloids, berberine was reported to inhibit hERG potassium current in transfected HEK cells expressing hERG channels [7][8][9], to block delayed rectifier potassium (I Kr ) current in cardiac myocytes [6], and to increase action potential duration on cardiac preparations [6,7]. Chelerythrine was also described to inhibit hERG current [10] and prolong action potential [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, berberine has no effect on inwardly rectifier K + channels (46). The similar K + channel blocking action was also observed for berberine within the same concentration range (IC 50 = 4.1 ìM) in cat ventricular myocytes (40). There are, however, conflicting reports in the literature on the effect of berberine on cardiac voltagegated Ca 2+ currents.…”
Section: Pharmacology Inotropic Effectmentioning
confidence: 72%
“…The current was detected also in other tissues, like vascular smooth muscle [16], embryonic xenopus muscle [17], vestibular dark cells [18], and pancreatic acinar cells [19]. Within a short period of time the current was identified in numerous vertebrate species, including shark [20], bullfrog [21,22], calf [23], rabbit [24], cat [25], guinea pig [26], dog [27] and men [28]. Sanguinetti and Jurkiewicz [29] demonstrated that the delayed rectifier current is composed of two distinct components namely; the rapid (I Kr ) and slow (I Ks ) components of I K .…”
Section: Role Of Delayed Potassium Currents In Cardiac Repolarizationmentioning
confidence: 98%